Heteromorphic Ni Foam@Ni(OH)2/MnO2 as a Self-Standing Electrode for Electro-Fenton Reactions. Issue 6 (9th April 2020) - Liu, Wenjing; Wu, Zhiyuan; Dong, Pei; Lin, Feifei; Zang, Meng; Qiao, Shuai; Gu, Yingying; Zhang, Jinqiang; Wang, Shuaijun; Zhao, Chaocheng
Abstract : Developing effective and economical materials for emerging electrochemical remediation of persistent organic pollutants has attracted significant research interest. In this study, a heteromorphic self-standing nickel foam@Ni(OH)2/MnO2 (NF@Ni(OH)2 /MnO2 ) electrode was synthesized by a simple solvothermal method and employed for the remediation of persistent organic pollutants. The prepared NF@Ni(OH)2 /MnO2 electrode exhibited better performance for the electro-catalytic degradation of tetracycline (TC) than that of the NF and NF@Ni(OH)2 . In optimized conditions, the NF@Ni(OH)2 /MnO2 electrode exhibited the highest TC degradation efficiency (90%) and total organic carbon(TOC) removal (59.02%) among the prepared electrodes. In addition, a higher mineralization current efficiency (MCE) and lower energy consumption (EC) for the NF@Ni(OH)2 /MnO2 electrode was achieved. The enhancement occurs primarily because the active MnO2 anchored to the porous and highly conductive Ni foam substrate surface boosts the electron transfer and the generation of hydroxyl radicals, as proved by a free radical trapping experiment and fluorescence spectrum analysis. This study suggests the possibility of a new paradigm in designing effective and practical electro-Fenton electrodes for environmental remediation.